2022
DOI: 10.3390/pharmacy10020041
|View full text |Cite
|
Sign up to set email alerts
|

Virtualized Gamified Pharmacy Simulation during COVID-19

Abstract: Extended and immersive gamified pharmacy simulation has been demonstrated to provide transformative learning in pharmacy education, preparing graduates for real-world practice. An international consortium of universities has implemented local adaptations of the Pharmacy Game into their curricula. From early 2020, pharmacy academics modified the delivery of gamified simulation in response to the COVID-19 pandemic, while still aiming to deliver the important learning outcomes of enhanced communication, collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Third, recent studies showed the potential benefits of integrating Chatbots, such as ChatGPT, in pharmacy education [49]. One of the main advantages of using ChatGPT in…”
Section: Discussionmentioning
confidence: 99%
“…Third, recent studies showed the potential benefits of integrating Chatbots, such as ChatGPT, in pharmacy education [49]. One of the main advantages of using ChatGPT in…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacy Game was the obvious outlier in this category, using a hybrid online delivery built around group interaction, with the need for extensive coordination between a team of users (facilitators and students). To facilitate the activity, they relied heavily on several separate Microsoft applications, such as Microsoft Teams, Microsoft Forms, Microsoft Excel and Microsoft Power Apps [ 85 ]. This may adversely affect staff time and effort required to deliver the exercise and introduces a dependency on these applications/services being available to the users—although presumably similar results could be achieved by selecting an appropriate set of competitor products.…”
Section: Discussionmentioning
confidence: 99%
“…Digital or computer data analytics may provide a source of objective data on student engagement and performance in activity, as evidenced in the review by Barber et al [24] This aligns well with the 2022 research in which authors provided details on using digital analytics to monitor student participation, engagement and performance during gamified pharmacy simulation. [92] Education research does not appear to be approached with the same degree of planning and rigour as other types of pharmacy research. There was an absence of randomised controlled trials, and the inclusion of only one study reporting a control group, which confirms the findings of the broad review of gamification in health professions education published by van Gaalen et al [14] In this current review, the lack of control was sometimes acknowledged by authors as a limitation of their work, and a gap in objective data collection.…”
Section: Discussionmentioning
confidence: 99%